Load frequency control with the penetration of renewable energy sources - Mohamed Hairutz Selamat (Nanyang Technological University, 2022)
Over the years, there have been continuous development all around the world and the most important aspect needed is energy. When the world keeps progressing ahead, there needs to be an increase in the demand for fossil fuels. The higher the demand, the quicker the nonrenewable sources would be depleted; therefore, it has become an important factor for us to develop large-scale renewable energy sources to be utilized for energy consumption. Renewable energy sources are good not only because of its reusability, but it is a cleaner alternative which helps to reduce carbon footprints left by carbon dioxide produced by burning fossil fuels. The renewable source that will be focused on in this project is wind energy, as it is one of the rapidly growing energy sources in the world. The purpose of this project is to be able to reduce the faults that might occur due to the unbalance of load due to the difference of power drawn on one side of the panel compared to the other side [1]. This happens because the frequency is not maintained at its optimal value of ±0.5 from the main frequency of 50Hz, Singapore standard. The scope of this project is to find and design a power system using wind energy generation by including the load frequency control be able to control the difference in frequency, to make it within range of 49.5Hz to 50.5Hz, while maintaining the real power balance of the system.